MARITAL INTERACTION AND MARITAL ROLE ON MARITAL SATISFACTION OF DUAL EARNER FAMILY WITH SCHOOL AGE CHILDREN - Desi Wulansari; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Lack of interaction and communication between husband and wife in various aspects of family life will cause conflict and disharmony. The purpose of the study was to identify interactions, husband-wife roles, and marital satisfaction of dual earner families with school children. The study involved 60 families consisting of 30 husbands and 30 non-partnered wives who are workers in Bandung Regency, West Java. Data were collected online using voluntary sampling technique. Husband-wife interaction was in the moderate category, husband-wife roles were in the low category for husbands and moderate for wives, and marital satisfaction was in the moderate category. The correlation test results show that there is a positive significant relationship between family income, husband-wife interaction, and husband-wife roles with marital satisfaction. The regression test results show that age, husband-wife interaction, the bonding and balanced relationship dimensions of the husband-wife interaction variable, and the social activity dimension of the husband-wife role variable have a positive effect on marital satisfaction. In increasing marital satisfaction, husband and wife are expected to be good at managing emotions, adjusting themselves, maintaining conjugal interactions, strengthening bonding and balanced relationships, and carrying out social activities.